Clinical study of patients with inguinal hernia at a tertiary care hospital - J., Pradeep Kumar; Kadli, Suresh; T., Kailas C.; Kadli, Sowmya (International Surgery Journal, 2017)
Background: The history of hernia is the history of surgery. Historically hernia causative was attributed to a mechanical disparity between visceral pressure and the resistance of the musculature. Methods: 100 cases of inguinal hernia admitted in Medical College Teaching Hospitals were selected on the basis of the nonprobability (purposive) sampling method. All patients with uncomplicated direct and indirect hernias treated by open approach surgeries were included. The age/sex incidence, mode of presentation, precipitating factors, surgical treatment, postoperative complications were all evaluated and compared with standard published literature. A predesigned proforma was used to collect this information for individual case. Results: The incidence of hernia was common in younger,18-40-year age group (33%), people engaged in agriculture (42%), labourers (33%). 52% patients presented with swelling and 48% with pain and swelling. Right indirect hernia was the most common (41%), right direct hernia (23%), pantaloon (7%) and bilateral in 8%. 32% patients had strenuous work as a precipitating factor, 35 % had smoking as associated factors. Abdominal tone was poor in 8% cases. Conclusions: Strenuous work is often responsible for development of hernia. Heavy work, especially lifting weights, puts a great strain on the abdominal muscles. If there is an underlying weakness already present, hernia may develop. The patient relates the onset of the hernia to a particular event.